2012
DOI: 10.1097/aud.0b013e31825c05ac
|View full text |Cite
|
Sign up to set email alerts
|

Tone-Burst and Click-Evoked Otoacoustic Emissions in Subjects With Hearing Loss Above 0.25, 0.5, and 1 kHz

Abstract: The results of this study indicate that a 0.5-kHz TBOAE is a more powerful test than the standard CEOAE when cochlear function at low frequencies is of interest. The 0.5-kHz TBOAE may be used to identify partial deafness in patients who generally fail to show a response to the commonly used clicks. In addition, use of 1/2 octave-band filtering can increase the reproducibility and power of the test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Several studies have demonstrated a relationship between audiometric status and OAEs. This relationship has been observed for DPOAEs (e.g., Gorga et al 1993; Stover et al 1996; Boege and Janssen 2002; Johnson et al 2010; Kirby et al 2011) CEOAEs; (e.g., Gorga et al 1993; Prieve et al 1993; Hussain et al 1998; Goodman et al 2009; Mertes and Goodman, 2013), SFOAEs (e.g., Ellison and Keefe 2005), and TBOAEs (e.g., McPherson et al 2006; Jedrzejczak et al 2012). As a consequence of the relationship between auditory status and OAEs, and because of their non-invasive nature, OAEs are used clinically, including in newborn hearing screening.…”
Section: Introductionmentioning
confidence: 52%
“…Several studies have demonstrated a relationship between audiometric status and OAEs. This relationship has been observed for DPOAEs (e.g., Gorga et al 1993; Stover et al 1996; Boege and Janssen 2002; Johnson et al 2010; Kirby et al 2011) CEOAEs; (e.g., Gorga et al 1993; Prieve et al 1993; Hussain et al 1998; Goodman et al 2009; Mertes and Goodman, 2013), SFOAEs (e.g., Ellison and Keefe 2005), and TBOAEs (e.g., McPherson et al 2006; Jedrzejczak et al 2012). As a consequence of the relationship between auditory status and OAEs, and because of their non-invasive nature, OAEs are used clinically, including in newborn hearing screening.…”
Section: Introductionmentioning
confidence: 52%
“…OAEs require the proper functioning of outer hair cells [ 9 ]. Because OAEs are very sensitive to cochlear abnormalities [ 10 ], their measurement is an excellent tool for monitoring cochlear status, such as after application of ototoxic drugs [ 11 ] or exposure to noise [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way as for WWR, usually the ears with larger response levels also had higher SNRs, although there were some appreciable differences between ears. The most common criterion for the presence of TEOAEs used in screening is SNR >3 or 6 dB [ 26 , 27 ], and these criteria are shown in Figure 4 . At a frequency of 1 kHz, both criteria were satisfied in all measurements for all ears.…”
Section: Resultsmentioning
confidence: 99%